14.0k views
0 votes
please answer all the questions! also show work and specify which answers belong to which problems/sections. thank you so much! :)

please answer all the questions! also show work and specify which answers belong to-example-1
User Ryan K
by
4.3k points

1 Answer

6 votes

Answer:

Explanation:

m =
(y_(2) -y_(1) )/(x_(2) -x_(1) )

(a). (- 3, 7)

(- 1, 13)

m =
(13-7)/(-1+3) = 3

y - 13 = 3(x - 1)

y = 3x + 10

(b). (12, 10)

(8, 12)

m = -
(1)/(2)

y - 12 = -
(1)/(2) (x - 8)

y = -
(1)/(2) x + 16

Now is your turn. You can do it!!

User Micael Levi
by
4.5k points